Answer:
Vertices A B y C
A ( 2 , 3 ) B ( -1 , 1 ) C ( 3, 1 )
Step-by-step explanation:
We have to solve a two-equation system, by pair of equations as follows
equation (1) 2x - 3y + 5 = 0
equation (2) 2x + y -7 = 0
Solving this system we find let´s say vertex A
0x - 4y +12 = 0 y = 3
Then x ?
2x - 3y + 5 = 0
2x - 9 + 5 = 0 ⇒ 2x = 4 x = 2
Then vertex A ( 2 , 3 )
From equation (1) and (3)
2x - 3y + 5 = 0
2x + 5y - 3 = 0
Agan subtracting (1) - (2)
0x -8y + 8 = 0
y = 1 and
2x + 5y = 3
2x + 5 = 3
2x = -2
x = -1
Vertex B ( -1 , 1 )
Finally from equation (2) and (3) we get the third vertex C
2x + y - 7 = 0
2x + 5y - 3 = 0
0x -4y -4 = 0
y = 1
2x + y = 7
2x + 1 = 7
2x = 6
x = 3
C ( 3 , 1 )